Penerapan Prinsip-prinsip Penilaian Perkembangan Anak Usia Dini di TK An-Nur II Maguwoharjo - Rahmawati, Miya (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
This study aims to look at the application of the principles of early childhood developmentassessment at TK Annur II Maguwoharjo, using a qualitative research approach with descriptive research type. states that qualitative research. The study was conducted at TK Annur II Maguwoharjo. The subjects of the study were the principal and teachers at TK Annur II Maguwoharjo. The object of the study was the application of the principles of early childhood development assessment at TK Annur II Maguwoharjo. There are 2 data collection methods, namely interviews and observations. The results obtained from the application of the principles of early childhood development assessment at TK Annur II Maguwoharjo are already done by the teacher well. Supporting factors are competent teachers and principals who on average have the qualifications of undergraduate education and routinely attend training programs of learning activities from elementary to advanced, and pass on the knowledge gained to colleagues in the school. The inhibiting factor is the number of indicators that must be observed by the teacher in detail